Reinvestigation of the structure-activity relationships of isoniazid - Hegde, Pooja (Tuberculosis (Edinb), 2021)
Isoniazid (INH) remains a cornerstone for treatment of drug susceptible tuberculosis (TB), yet the quantitative structure-activity relationships for INH are not well documented in the literature. In this paper, we have evaluated a systematic series of INH analogs against contemporary Mycobacterium tuberculosis strains from different lineages and a few non-tuberculous mycobacteria (NTM). Deletion of the pyridyl nitrogen atom, isomerization of the pyridine nitrogen to other positions, replacement of the pyridine ring with isosteric heterocycles, and modification of the hydrazide moiety of INH abolishes antitubercular activity. Similarly, substitution of the pyridine ring at the 3-position is not tolerated while substitution at the 2-position is permitted with 2-methyl-INH 9 displaying antimycobacterial activity comparable to INH. To assess the specific activity of this series of INH analogs against mycobacteria, we assayed them against a panel of gram-positive and gram-negative bacteria, as well as a few fungi. As expected INH and its analogs display a narrow spectrum of activity and are inactive against all non-mycobacterial strains evaluated, except for 4, which has modest inhibitory activity against Cryptococcus neoformans. Our findings provide an updated analysis of the structure-activity relationship of INH that we hope will serve as useful resource for the community.